Analisis penerapan penguatan permodalan oleh Otoritas Jasa Keuangan di PT. Bank SulutGo - Eman, Golda Amelia; Karamoy, Herman; Lambey, Robert (Yayasan Widyantara Nawasena Raharja, 2024)
This study is based on of the latest policy by the Financial Services Authority through POJK No. 12/POJK.03/2020 concerning Commercial Bank Consolidation to maintain the stability of the financial and banking sector from the impact of the economic and monetary crisis. The object of this study is PT. Bank SulutGo as a bank of North Sulawesi Province in Indonesia. This POJK regulates the increase in Minimum Core Capital for Commercial Banks which will be carried out in stages from 2020 to 2022 amounting to IDR 3 trillion and for Regional Development Banks (BPD) until 31 December 2024. This research uses a qualitative research method which explains descriptively the analysis of the phenomenon of banking development, especially PT. Bank SulutGo due to the implementation of OJK new regulations using data in the form of narratives and Banking Financial Performance Reports. The shareholders over the last three years have made efforts to deposit capital and increase their share ownership, but it is predicted that until 2024, PT. Bank SulutGo has not been able to meet the bank's minimum core capital of Rp. 3 trillion. In order not to be affected by the OJK's exit policy, PT. Bank SulutGo can choose a consolidation strategy for going concern, the consolidation strategy is appropriate for PT. Bank SulutGo in complying with OJK regulations is forming a Joint Business Group (KUB).